Sistem Informasi Bidang Sarana Disporasu Berbasis Website Menggunakan Framework Bootstrap - Gunawan, Jaka; Triase, Triase; Abdillah, Muhammad Dimas (Jurnal Ilmiah Sains dan Teknologi, 2024)
The North Sumatra Province Youth and Sports Service is one of the government agencies that oversees the fields of youth services, partnership services and sports services in North Sumatra. Previously, the process of collecting contract documents and procurement of goods was carried out by manually inputting all transactions using the Microsoft Excel program. Bootstrap is a framework used to build responsive and attractive websites and is built by applying database development methods via phpMyAdmin, building program websites via Visual Studio Code using HTML, CSS, PHP, and Xampp. The system creation stage consists of analysis, UML design, database design, and the implementation. So that the Web-Based Information System for Disporasu Facilities, which was built using the Bootstrap framework, can process data smoothly, quickly, with minimal errors, and the information needed about contract documents and sporting goods can be obtained easily.